2021
DOI: 10.5194/esd-2021-90
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid attribution analysis of the extraordinary heatwave on the Pacific Coast of the US and Canada June 2021

Abstract: Abstract. Towards the end of June 2021, temperature records were broken by several degrees Celsius in several cities in the Pacific northwest areas of the U.S. and Canada, leading to spikes in sudden deaths, and sharp increases in hospital visits for heat-related illnesses and emergency calls. Here we present a multi-model, multi-method attribution analysis to investigate to what extent human-induced climate change has influenced the probability and intensity of extreme heatwaves in this region. Based on obser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
134
2
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 44 publications
3
134
2
4
Order By: Relevance
“…Some of this water vapour accumulated under a ridge of high pressure and may have formed a positive feedback loop to enhance the heatwave development over western NA during late June and early July 2021. A rapid attribution analysis has pointed out that that the occurrence of this extreme heatwave is virtually impossible without human-caused climate change 41 . Our results provide evidence that moisture must be considered when assessing heatwave development in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of this water vapour accumulated under a ridge of high pressure and may have formed a positive feedback loop to enhance the heatwave development over western NA during late June and early July 2021. A rapid attribution analysis has pointed out that that the occurrence of this extreme heatwave is virtually impossible without human-caused climate change 41 . Our results provide evidence that moisture must be considered when assessing heatwave development in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…S4), the extreme heatwave started in Washington State and spread rapidly southward into Oregon and northward across BC and Alberta in western Canada. It generated some of the highest temperatures ever recorded in this region, including the new Canadian record of 49.6°C measured at Lytton, BC on June 29, 2021 41 .…”
Section: The Possible Ar Impact On the Western North America Heatwavementioning
confidence: 99%
See 1 more Smart Citation
“…Rapid attribution analyses found that this historic event would have been virtually impossible without anthropogenic climate change. 1 Hundreds of local temperature records were broken, often on consecutive days at the same location. For example, the small town of Lytton in the Fraser Canyon broke national temperature records on June 27 (46.6°C), June 28 (47.5°C), and June 29 (49.6°C) before being destroyed by wildfire on June 30.…”
Section: Introductionmentioning
confidence: 99%
“…Whether focusing on communities living in hot, tropical climates or those in cooler, mid-latitude climates, there exists clear evidence of the manifold risks associated with extreme high temperatures, including for human health (Gasparrini et al 2015; Vicedo-Cabrera et al 2021), animal welfare (Bryant et al 2007;Dunn et al 2014) and economic productivity (Steffen et al 2019). Similarly stark evidence shows both the frequency and intensity of extreme heat events are increasing worldwide, in response to anthropogenic climate change (Vogel et al 2019;Harrington 2021a; Philip et al 2021). Despite this globally ubiquitous evidence base, extreme heat remains chronically understudied in New Zealand.…”
Section: Introductionmentioning
confidence: 99%